Evaluation of Community-level Effects of Communities That Care on Adolescent Drug Use and Delinquency Using a Repeated Cross-sectional Design - Rhew, Isaac C. (Prev Sci, 2016)
The Communities That Care (CTC) prevention system has shown effects on reducing incidence and prevalence of problem behaviors among a panel of youth followed from 5th through 12th grade. The present report examines whether similar intervention effects could be observed using a repeated cross-sectional design in the same study. Data were from a community-randomized trial of 24 U.S. towns. Cross-sectional samples of 6th, 8th, and 10th graders were surveyed at four waves. Two-stage ANCOVA analyses estimated differences between CTC and control communities in community-level prevalence of problem behaviors for each grade, adjusting for baseline prevalence. No statistically significant reductions in prevalence of problem behaviors were observed at any grade in CTC compared to control communities. Secondary analyses examined intervention effects within a “pseudo cohort” where cross-sectional data were used from 6th graders at baseline and 10th graders four years later. When examining effects within the pseudo cohort, CTC compared to control communities showed a significantly slower increase from 6th to 10th grade in lifetime smokeless tobacco use, but not for other outcomes. Exploratory analyses showed significantly slower increases in lifetime problem behaviors within the pseudo cohort for CTC communities with high, but not low, prevention program saturation compared to control communities. Although CTC demonstrated effects in a longitudinal panel from the same community-randomized trial, we did not find similar effects on problem behaviors using a repeated cross-sectional design. These differences may be due to a reduced ability to detect effects because of potential cohort effects, accretion of those who were not exposed, and attrition of those who were exposed to CTC programming in the repeated cross-sectional sample.